2003
DOI: 10.1007/s00122-003-1353-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci associated with ultraviolet-B resistance in rice (Oryza sativa L.)

Abstract: The detection of quantitative trait loci (QTLs) associated with UV-B resistance in rice should allow their practical application in breeding for such a complex trait, and may lead to the identification of gene characteristics and functions. Considerable variation in UV-B resistance exists within cultivated rice (Oryza sativa L.), but its detailed genetic control mechanism has not been well elucidated. We detected putative QTLs associated with the resistance to enhanced UV-B radiation in rice, using 98 BC(1)F(5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…The heading date and waxiness of the grain (Olsen et al 2006) are thought to be artificially selective traits. As QTLs in upland/ lowland marker regions, QTL for phosphorous sensitivity (Wissuwa et al 1998) near RM207, field resistance for rice blast near RM418 (Tabien et al 2002), spikelet number, amylose content (Cui et al 2002) and allelopathy (Ebana et al 2001) near RM412, UV-B resistance (Sato et al 2003) near RM516, culm strength under upland conditions (Mu et al 2004) near RM440, were reported. These QTLs seem related to the upland and lowland cultivation conditions or differences among the morphological differences of upland and lowland varieties.…”
Section: Discussionmentioning
confidence: 99%
“…The heading date and waxiness of the grain (Olsen et al 2006) are thought to be artificially selective traits. As QTLs in upland/ lowland marker regions, QTL for phosphorous sensitivity (Wissuwa et al 1998) near RM207, field resistance for rice blast near RM418 (Tabien et al 2002), spikelet number, amylose content (Cui et al 2002) and allelopathy (Ebana et al 2001) near RM412, UV-B resistance (Sato et al 2003) near RM516, culm strength under upland conditions (Mu et al 2004) near RM440, were reported. These QTLs seem related to the upland and lowland cultivation conditions or differences among the morphological differences of upland and lowland varieties.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the uniformity of the genetic background of each CSSL enabled to rapidly proceed to the linkage mapping of target QTLs. We have already revealed the advantages of these CSSLs in the analysis of resistance to ultraviolet-B radiation (Sato et al 2003, Ueda et al 2004, the response of rice to Al (Ma et al 2002), and seed longevity (Miura et al 2002).…”
Section: Cssls As Experimental Materialsmentioning
confidence: 99%
“…The study identified three QTLs on chromosomes 1, 3 and 10. Among them, qUVR-10, a qtl for UVB resistance on chromosome 10, showed the largest effect (the percentage of variance explained was approximately 40%) and plants homozygous for the "Nipponbare" allele at this QTL locus were more resistant to UVB compared with those homozygous for the "Kasalath" allele (63). After the QTL cloning, qUVR-10 was shown to encode cPD photolyase (72,73).…”
Section: Genetic Approaches To Understanding Cultivar Differences In mentioning
confidence: 99%